SP3.1.17 Assessment of the utility of CT to predict the requirement for resection at laparotomy in patients presenting with acute mesenteric arterial insufficiency. (28th October 2021) - Ng, James; Hennessy, Martin; Hussey, Keith
Abstract: Introduction: Mesenteric ischaemia as a consequence of arterial atherosclerosis is associated with significant morbidity and mortality. Practice has been influenced by the rise in cross-sectional imaging. In Glasgow a policy of laparotomy for patients presenting with acute mesenteric ischaemia at the time of mesenteric revascularisation has been adopted. We have sought to define whether CT can predict visceral necrosis and a requirement for tissue resection at the primary revascularisation. Methods: This was a retrospective review of interventions performed for mesenteric ischaemia. Radiological variables described in the context of mesenteric ischaemia were defined. The primary CT report was reviewed to define whether these features were recorded and whether a diagnosis of mesenteric ischaemia was suggested. Imaging was then retrospectively reviewed with reference to the dataset by a radiologist. The radiologist was asked to offer a subjective opinion as to whether there was mesenteric infarction. These data were compared with laparotomy findings. Results: There were 129 interventions performed for mesenteric ischaemia over the study period and 147 laparotomies. There was no specific radiological variable that was consistently reported in the primary or secondary CT review. However when bowel wall thinning, hypoattenuation or portal venous gas reported (independently) they seemed to be specific as in each case there was mesenteric infarction at laparotomy. Conclusion: Even with retrospective radiological assessment there is no reliable feature that will predict mesenteric infarction and a requirement for tissue resection. As such a policy of laparotomy in patients who considered physiologically well enough would appear to be justified.